E-learning system for autistic children - Shukur, Ban Salman (2011)
In general, children with autism may have with social/emotional relationships problems, problems with communication, trouble with surroundings, consciousness problems and cognitive problems. The purpose this study is to help autistic children learn alphabets in the early levels of learning. With this paper, we hope to propose an e-learning school-base system for autistic children of education ages between 4-6 years.In addition, our system will enable teachers to teach one or more children at the same time.